The costs and benefits of enrolling in an academically matched college. (April 2016) - Howell, Jessica S.; Pender, Matea
Highlights: Low-income students face very little tradeoff between net price and BA completion when choosing a college. BA completion by low-income students rises when they attend better matched colleges. The financial impact of expanding enrollment to improve low-income students' match is non-trivial. Accommodating these students has minimal impact on physical capacity or average metrics. Abstract: In response to increased efforts to raise college completion rates through improved academic match between students and their colleges, we examine the costs and benefits to students of following such advice as well as the impact on postsecondary institutions. We analyze data from the National Postsecondary Student Aid Study, the College Board, the National Student Clearinghouse, and the Integrated Postsecondary Education Data System to estimate the impact of improved academic match on students' predicted net price and bachelor's completion probabilities. The results indicate that undermatching low-income students across the distribution of academic ability would experience a substantial boost in bachelor's degree completion probability – 13.5% points, on average – if they attended a college that better matched their academic credentials. Given this average effect and the number of undermatched low-income students who are minimally "treated" under our simulation, we predict that an additional 3500 low-income students per cohort would complete a bachelor's degree. We find that moving all undermatched low-income students into "safety" colleges would not overly burden this set of institutions, which, on average, would only need to increase the size of first-year cohorts by less than 1%. Moreover, such colleges would experience no change in average SAT scores and overall graduation rates. One estimate of the financial impact on colleges is substantial (i.e., on average, 6.5 M–7.5 M annually per cohort per institution that has a simulated net gain in enrollment) if institutions cover full tuition and fees for these additional low-income students.